South East Asian (SEA) Games Biomechanics Project - Wei, X.; Chuan, T. K.; Raynor, A. J.
The 19th SEA Games were held in Jakarta, Indonesia in October 1997 and presented an ideal opportunity for much needed kinematic data to be collected from the track and field athletes representing the ten South East Asian countries. The quantitative data obtained from high speed video cameras will be used to provide coaches and athletes with information to further improve their performance. Method Two- and three-dimensional video data was collected at 50 and 200 fields/sec using two Peak Motus motion analysis systems. The men's javelin, hammer throw and discus events were recorded using a fixed 3-camera system, while the women's and men's 100 m sprints, 110 m hurdles and triple jump events were recorded using a two camera pan and tilt system. As an example of the data collected, the men's hammer throw gold medallist was analyzed. The three cameras were placed to provide a rear, lateral and left-frontal view, with the reference origin being the centre of the throwing circle: X (anterior-posterior), Y (medio-lateral), Z (vertical). The position of the hammer, resultant velocity and angle of projection (with respect to horizontal) were measured at the instant of release. Results The hammer was thrown distances ranging from 53.22m to 58.00m by the gold medallist. At the point of release the position of the hammer ranged from 0.75-0.88 m (X), -2.02-(-1.58) m (Y) and 1.62-1.90 m (Z) with a resultant velocity of 23.3-24.3 m/s and an angle of projection of 41.0-44.2 degrees. Conclusion The major difference observed when comparing the SEA Games gold medallist with world class throwers was the lower release velocity of the SEA Games athletes. As a practical research project, the major problems encountered were obtaining access to the field for video recording, transport of equipment, ensuring stable power supply and equipment failure.